Aggregation of Rare Earth Coordination Complexes in Solution Studied by Paramagnetic and DOSY NMR. Issue 60 (9th October 2018) - Poh, Adeline W. J.; Aguilar, Juan A.; Kenwright, Alan M.; Mason, Kevin; Parker, David
Abstract: The degree of aggregation of neutral, 9‐coordinate rare earth coordination complexes has been shown to affect their ligand field, as revealed by diffusion‐ordered NMR spectroscopy (DOSY‐NMR) measurements on Y(III) complexes, paramagnetic NMR analyses of Yb and Tb analogues and emission spectral studies with the Eu III systems. In non‐polar media a lipophilic tris‐isopropyl complex, [Ln.L 2 ] tends to aggregate in chloroform and dichloromethane giving rise to oligomers, whereas in acetic and trifluoroacetic acid the more polar parent complex, [Ln.L 1 ], also aggregates, profoundly affecting the pseudocontact shift and the form of the Eu emission spectrum. Such behaviour has important implications in the design of responsive spectral probes. Abstract : DOSY‐do : The degree of aggregation of neutral, 9‐coordinate rare earth coordination complexes has been shown to affect their ligand field, as revealed by diffusion‐ordered NMR spectroscopy. This work highlights the great scope that exists for creating NMR and optical spectral probes of the chemical environment with lanthanide complexes.